Chemical Design for Both Molecular and Morphology Optimization toward High‐Performance Lithium‐Ion Batteries Cathode Material Based on Covalent Organic Framework. (9th September 2021) - Wu, Manman; Zhao, Yang; Zhao, Ruiqi; Zhu, Jie; Liu, Jie; Zhang, Yamin; Li, Chenxi; Ma, Yanfeng; Zhang, Hongtao; Chen, Yongsheng
Abstract: In most cases, to obtain high‐performance electrode materials for lithium‐ion batteries (LIBs), it is necessary to optimize both their molecular structure and morphology. Normally, the molecular structure of covalent organic frameworks (COFs) can be well engineered by chemical design, while their morphology is mainly optimized by post‐processing. Herein, by introducing a flexible building unit containing sp 3 N redox‐active centers, a bipolar‐type TP‐TA COF assembled by uniform 2D hexagonal nanosheets is synthesized in a one‐step reaction without any post‐processing, achieving the highly challenging simultaneous optimization of both molecular structure and morphology required for high‐performance electrode materials. Thus, when used as cathode material for LIBs, its combined optimized chemical structure and favorable morphology of TP‐TA COF synergistically render a high capacity (207 mA h g −1 at 200 mA g −1 ), excellent rate performance (129 mA h g −1 at 5.0 A g −1 ), and cycling stability (93% capacity retention after 1500 cycles at 5.0 A g −1 ). Abstract : By introducing a flexible building unit, a bipolar‐type covalent organic framework (TP‐TA COF) assembled using 2D hexagonal nanosheets is synthesized via a solvothermal method, achieving the simultaneous optimization of both molecular structure and morphology. When used as cathode material for lithium‐ion batteries, the combination of the bipolar‐type feature and favorable morphology of TP‐TA COF renders excellent overall performance.